2010
DOI: 10.1002/ejoc.201001130
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Baeyer–Villiger Oxidation of 2,3‐ and 2,3,4‐Substituted Cyclobutanones Catalyzed by Chiral Phosphoric Acids with Aqueous H2O2 as the Oxidant

Abstract: Catalytic asymmetric Baeyer-Villiger (B-V) oxidation of 2,3,4-trisubstituted cyclobutanone (4) has been realized by the catalysis of a 1,1Ј-bi-2-naphthol (BINOL)-derived chiral phosphoric acid (1j), which contains bulky 2,4,6-triisopropyl phenyl groups at the 3,3Ј-positions of the BINOL backbone, using 30 % aqueous H 2 O 2 as the oxidant, affording the corresponding γ-lactone (5) in 99 % yield with 95 % ee. In a divergent kinetic resolution of racemic 2,3-disubstituted bicyclic cyclobutanones (6) through asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 59 publications
1
20
0
2
Order By: Relevance
“… 272 Mechanistic studies suggested that chiral phosphoric acid plays the role of a bifunctional catalyst to activate both the reactants and the Criegee intermediate in a synergistic manner. 273 , 274 …”
Section: Assembly Of the Lactone Core Structurementioning
confidence: 99%
“… 272 Mechanistic studies suggested that chiral phosphoric acid plays the role of a bifunctional catalyst to activate both the reactants and the Criegee intermediate in a synergistic manner. 273 , 274 …”
Section: Assembly Of the Lactone Core Structurementioning
confidence: 99%
“…On the basis of their success on chiral phosphoric acid‐catalyzed desymmetric B‐V oxidation of 3‐substituted cyclobutanones (see Scheme ), Ding and co‐workers further explored the potential of chiral phosphoric acid catalysts in the B‐V oxidation of racemic 2,3‐disubstituted bicyclic cyclobutanones 30 using 30% aqueous H 2 O 2 as the oxidant . As is illustrated in Scheme , the enantioselective B‐V oxidation gave a range of chiral lactones in moderate to high NL/AL ratios with the NL products as the major regioisomers, when 10 mol% of chiral phosphoric acid 33 was used.…”
Section: Kinetic Resolutionmentioning
confidence: 99%
“…In addition, excellent reactivity was also observed in the oxidation of a 3,3‐disubstituted cyclobutanone, albeit only a moderate ee value was obtained for 42t . The authors also explored the potential of CPA in the desymmetric B‐V oxidation of a tricyclic cyclobutanone ( 43 ) and found that up to 95% ee and almost quantitative yield could be obtained when ( R )‐TRIP was used . Based on these results, they further investigated the charge‐transfer effect on this chiral phosphoric acid‐catalyzed asymmetric B‐V oxidation …”
Section: Desymmetrizationmentioning
confidence: 99%
“…Ding et al. recently extended their study to the BV oxidation of racemic bicyclic ketones, which exemplifies a process of divergent kinetic resolution 68. According to different migratory attitude of the ketonic alkyl moieties and asymmetric induction provided by the organocatalyst, two optically enriched lactones were formed in excellent yield and moderate regioisomeric ratio (Scheme ).…”
Section: Baeyer–villiger Reactionmentioning
confidence: 99%